2019
DOI: 10.1177/0145445519882894
|View full text |Cite
|
Sign up to set email alerts
|

Persuasive Quick-Writing about Text: Intervention for Students with Learning Disabilities

Abstract: Researchers examined the effects of self-regulated strategy development (SRSD) to teach students with learning disabilities (LD) to compose persuasive quick-writing about text. The study included a multiple-baseline design with multiple probes for eight students with LD in grades four and five. Researchers observed a functional relationship by systematically replicating the intervention across all student participants. Following SRSD instruction for paraphrasing text and persuasive quick-writing, students incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The study also found that when students were taught to use self-regulation strategies, such as setting goals and monitoring their progress, they were able to apply these strategies to other writing assignments and academic situations. Other studies [48][49][50] examined the effectiveness of a Self-Regulated Strategy Development (SRSD) approach to writing instruction for students with SLD. These studies found that students who received An SRSD Intervention Study for Students with Specific Learning Disabilities to Improve… DOI: http://dx.doi.org/10.5772/intechopen.112526 SRSD instruction showed significant improvement in their written expression, as well as in their ability to apply these strategies to new writing tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that when students were taught to use self-regulation strategies, such as setting goals and monitoring their progress, they were able to apply these strategies to other writing assignments and academic situations. Other studies [48][49][50] examined the effectiveness of a Self-Regulated Strategy Development (SRSD) approach to writing instruction for students with SLD. These studies found that students who received An SRSD Intervention Study for Students with Specific Learning Disabilities to Improve… DOI: http://dx.doi.org/10.5772/intechopen.112526 SRSD instruction showed significant improvement in their written expression, as well as in their ability to apply these strategies to new writing tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini memiliki perbedaan dengan penelitian terdahulu. Penelitian sebelumnya membandingkan praktik literasi kritis strategi QW dalam lingkungan belajar mengajar (Driessens & Parr, 2020), kemudian dalam situasi pembelajaran untuk siswa berkebutuhan khusus (Ciullo et al, 2021;Mason et al, 2011), dan dengan pembelajaran konvensional, walaupun penerapannya untuk aktivitas keterampilan menulis siswa kelas enam yang berbeda (Wati, 2019). Belum ada penelitian yang menggunakan strategi QW berbantuan media animasi untuk menilai kemampuan menulis teks persuasi siswa di jenjang SMP.…”
Section: A Pendahuluanunclassified
“…Using a multiple baseline design, Ciullo, Mason, and Judd (2019) investigated the effects of an intensive writing intervention for students with learning disabilities (LD) in the upper elementary grades. In this study, participants were provided instruction in self-regulated strategy development (SRSD) that focused on text paraphrasing and persuasive quick-writing.…”
mentioning
confidence: 99%